Experimental modelling of floating debris boom - Tan, Jo Ee (2015)
Rivers play an important role in providing the water resources for human and ecosystem survival and health. Nowadays, most urban areas experience difficulties in solving water pollution in rivers and streams. Hence, a proper solution should be carried out to overcome this problem. The objective of this research is to study an effective floating debris boom which can be created with appropriate dimensions, as well as good level of effectiveness of material in various flow rates, in a rectangular open channel to reduce the river pollution. In this research, there are two types of connection, hinged or drilled hole that will be used to connect the piers and the booms. Three types of material were used which are Styrofoam, bamboo, and PVC. Total six booms were created and tested with five different flow rates. An amount of 200g of debris was put into the open channel to test the floating debris boom. The results indicated that hinged connection is stronger than drilled-hole connection to connect the piers and the booms as it provided a free movement for the boom to move. For the type of material, Styrofoam proved that it has the best effectiveness for capturing the debris due to its lighter weight among the three materials. Based on the data obtained, floating debris boom which is made from Styrofoam and connected by hinged connection has the best performance and effectiveness for capturing the debris in this experiment. Eventually, this finding may contribute toward the minimization of river pollution happening in Malaysia.